A study on the perceived effectiveness of casino safeguards in Singapore. - Ho, Paul Chin Wee. (2008)
This study aims to measure both potential problem gamblers and non-problem gamblers’ perceptions on the effectiveness of the following four safeguards, namely, the Casino Entry Levies, the Voluntary Personal Exclusion Programme, the Family Exclusion Programme and the Voluntary Loss Limit System. English or Chinese versions of the survey questionnaire were administered to 240 Singaporeans aged above 21. The data collected were analysed using t-tests and stepwise multiple regressions. In addition, recommendations were made to improve the safeguards.